Performa alat pengering pakaian tipe portabel untuk mengeringkan pakaian (kaos) - Syamsuri Syamsuri; Bagus Cahyo Adi (TURBO [Tulisan Riset Berbasis Online], 2022)
The development of technology has triggered humans to learn knowledge science and increase innovation through various techniques. Basically, a drying system requires innovation so that it can work optimally and produce high efficiency of work. The use of cloth drying wardrobe will run well when its performance is also improved.This experimental research investigated the effects of drying time variation toward the efficiency of dryer system. In addition, it scrutinized the effects of drying time variation against the cloth weight inside the system. It also probed the drying percentage upon the T-shirt by varying the observation every 5 to 55 minutes.The research results demonstrated that the higher the heating time, the higher the system efficiency, exactly from 1.95% to 4.51%. Meanwhile, the higher the heating time, the lower the T-shirt weight, from 450 grams to 205 grams in which each required 55 minutes.